West-East technology transfer: internalizing global external effects - Birgit Sander (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Environmental pollution is a serious problem in Middle and Eastern Europe. Although most Middle and Eastern European countries since long have established extensive legislation on environmental issues, they rarely have enforced these laws. Virtually, they did not persue any effective environmental policy. Only with beginning of political and economic reforms the dimension of environmental damages has begun to be recognized, yet awareness has risen rapidly. Due to the process of political and economic opening, new opportunities for international cooperation are arising. This paper proposes a policy of internalizing the negative external effects of environmental pollution as well as the positive external effects of environmental protection. It takes up the elements of both the Pigouvian and the Coasean solution to external effects. A tax-subsidy scheme shall be used in the national context while a bargaining procedure shall be employed in the context of international cooperation. Subsidized West-East technology transfer will contribute to both improving environmental quality in all over Europe and to effectively support the process of reforms in Central-East Europe.
Keywords: 330; Umweltbelastung; Umweltschutz; Steuerbegünstigung; Technologietransfer; Externer Effekt; Westliche Staaten; Osteuropa